TAXONOMY AND DISTRIBUTION OF THE fAMILY CANDACIIDAE IN INDONESIAN COASTAL WATERS - Mulyadi Mulyadi (Treubia, 1997)
Some species of calanoid copepods of the family Candaciidae 'inhabit surface or moderately deep waters, provide excellent materials for a zoogeographic investigation. Very few studies partaining to the taxonomy and biogeography of the members of the family Candaciidae in Indonesian waters have been previously carried out. The present paper deals with relevant informations on description and illustrations of 14 candaciid speciesfrom this region. All the previously known species have been found, one species Candacia ishimarui is new to science, and one C. guggenheimi Grice and Jones, 1960 is new records. A catalogue of all the nominal species (both valid species and synonyms) hitherto described from the world oceans, the zoogeography and a key of these species is discussed.